Nutritional status and systemic inflammation in COPD: prognostic value of the advanced lung cancer inflammation index - Yao, Jun; Wu, Peng; Li, Zhishu; Zhao, Lingyan; Fu, Ziqiao; Shi, Ping; Xiong, Xiaomin; Chen, Xuping; Yu, Bin; He, Yan; Feng, Tong; Zeng, Jia; et al. (Frontiers in Nutrition, 2025)
BackgroundChronic Obstructive Pulmonary Disease (COPD) is a leading cause of global mortality, with systemic inflammation and malnutrition playing pivotal roles in its progression and outcomes. The Advanced Lung Cancer Inflammation Index (ALI), which integrates nutritional status and systemic inflammation, may offer potential prognostic value in COPD management.ObjectivesThis study aimed to evaluate the relationship between ALI and mortality outcomes in COPD patients, with a specific focus on the interplay between nutrition, inflammation, and their non-linear associations with all-cause and cardiovascular mortality.MethodsData were derived from the NHANES (1999–2018) cohort, comprising 47,880 participants, including 1,960 COPD patients. ALI was calculated using body mass index (BMI), serum albumin levels, and the neutrophil-to-lymphocyte ratio (NLR). Survival analyses, including Kaplan–Meier curves, Cox proportional hazards models, and restricted cubic splines, were used to assess the association between ALI and mortality outcomes, exploring non-linear trends and thresholds.ResultsHigher ALI levels were significantly associated with reduced risks of all-cause and cardiovascular mortality in COPD patients. Protective effects plateaued at ALI thresholds (88.32 for all-cause mortality and 89.73 for cardiovascular mortality), with mortality risks reversing at excessively high levels for cardiovascular mortality.ConclusionALI, as a composite marker of nutritional status and systemic inflammation, is a valuable prognostic tool for COPD patients. Its non-linear relationship with mortality underscores the need to optimize nutritional and inflammatory management strategies. These findings emphasize the critical importance of addressing malnutrition and systemic inflammation to improve COPD outcomes. Future research should validate these findings and investigate tailored nutritional interventions and anti-inflammatory treatments.